AFGHANISTAN-UZBEKISTAN RELATIONS: A NEW STAGE OF COOPERATION (TAMADDUN NURI JURNALI, 2024)
This article analyzes the relations between Afghanistan and Uzbekistan on a historical and modern basis and covers the issues of development of the two countries, ensuring political and economic stability. Work has been shown to strengthen cultural and educational cooperation between Afghanistan and Uzbekistan.